2017
DOI: 10.1039/c6cp02504h
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual density functional theory for electron transfer and transport in mesoscopic systems

Abstract: Molecular and supramolecular systems are essentially mesoscopic in character. The electron self-exchange, in the case of energy fluctuations, or electron transfer/transport, in the case of the presence of an externally driven electrochemical potential, between mesoscopic sites is energetically driven in such a manner where the electrochemical capacitance (C) is fundamental. Thus, the electron transfer/transport through channels connecting two distinct energetic (ΔE) and spatially separated mesoscopic sites is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In the presence of an electrolyte, the associated potential of the gate is screened by the environment, which is illustrated by solvent molecules now surrounding the electrochemical capacitance, C μ̅ , instead of C μ . Thus, C μ̅ now replaces C μ as the series association of ionic (double-layer as a typical exemplar) and quantum capacitors , (see more details below), thus constituting the missing physical structure of interest to interpret the time-dependent (or the time-scale) response of molecular electronics , (attended in an electrolyte environment) and molecular electrochemistry. , When an electrolyte is present, the electrical field screening is a critical aspect , because the solvent chemical environment is essential to dictate the electron dynamics, according to electron transfer models. , …”
Section: Charge Relaxation and Chemical Capacitancementioning
confidence: 99%
See 3 more Smart Citations
“…In the presence of an electrolyte, the associated potential of the gate is screened by the environment, which is illustrated by solvent molecules now surrounding the electrochemical capacitance, C μ̅ , instead of C μ . Thus, C μ̅ now replaces C μ as the series association of ionic (double-layer as a typical exemplar) and quantum capacitors , (see more details below), thus constituting the missing physical structure of interest to interpret the time-dependent (or the time-scale) response of molecular electronics , (attended in an electrolyte environment) and molecular electrochemistry. , When an electrolyte is present, the electrical field screening is a critical aspect , because the solvent chemical environment is essential to dictate the electron dynamics, according to electron transfer models. , …”
Section: Charge Relaxation and Chemical Capacitancementioning
confidence: 99%
“…The latter is the case where the charge of the mesoscopic (or molecular) scale capacitance is embedded in an electrolyte environment, like that depicted in Figure b . This obviously corresponds to the time-scale of the electrochemical reaction conforming to a single electron transfer such as , where k is the well-known electron transfer rate constant. Equation is validated in ref and thus represents the quantum RC circuit model for electrochemistry at room temperature.…”
Section: Electron Transfer Rate and Electrochemical Capacitancementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been a growing interest in the development of optimized interfaces capable of supporting the detection of clinically relevant analytes, especially those translatable to rapid low cost analyses. Derived immunosensors , (which translate a biological biomarker recognition into a measurable signal) have been based on a variety of electrochemical techniques, such as voltammetry, amperometry, , and electrochemical impedance spectroscopy (EIS). EIS is a natively spectroscopic and highly sensitive method within which interfacial charge transfer resistance R ct is most commonly assessed as a reporter of analyte recognition. , Recently we introduced electrochemical impedance-derived capacitive spectroscopy , as a label-free, reagentless method of mapping the change in interfacial redox capacitance ( C r ) as a transducer, omitting the need for a solution phase redox-probe. , The partition of mobile electrons between an electrode and a surface tethered chargeable (redox or quantum) species generates a spectroscopically resolvable capacitance. We have shown that this interfacial signal is fundamentally quantum mechanical in nature and that the charging signature is highly sensitive to changes in local environment. ,, When incorporated into a redox addressable molecular film capable of selectively binding an analyte, C r can (where the binding site is in close proximity) become a sensitive function of target concentration. To date, such interfaces have been created by covalent immobilization of bioreceptors within a mixed self-assembled monolayer (SAM), one film component being redox active, the second serving as a receptor anchor. ,, …”
mentioning
confidence: 99%